The effects of business strategies on the financial performance of the rubber and plastic industries - Villarreal Archila, Sylvia María; Pardo Pérez, Karen Sofía (Cuadernos de Administración, 2020)
The following article is meant to analyze from a qualitative and quantitative approach the effects of business strategies on the financial performance of small, medium and large companies in the plastic and rubber industry at the Bucaramanga Metropolitan Area.The research began by compiling the financial indicators available at Cámara de Comercio de Bucaramanga to, later on, apply a Likert-type survey to characterize the strategic orientation and performance of the companies during 2017. This information was statistically analyzed using the SPSS software. A cluster and an ANOVA analysis were carried out with the following indicators: competitive factors, perception of effectiveness, ROA and ROE. After the analysis, it was possible to determine that 58% of the companies have an analytical strategic orientation, followed by a 31.5% of companies with a defensive profile, and 10.5% of companies with a prospective one. While the operating margin is the most influential factor, the growth rate is the one with the most significant variation according to entrepreneurs’ perception. Researchers determined that companies’ strategies do not influence the assets turnover, debt ratio, internal leverage, return on assets and operating margin; however it was possible to notice a positive relationship between external leverage indicators and return on equity. This research serves as a foundation for future academic exploration in one of the economic sectors that currently demand the most critical challenges in terms of environmental awareness.